Food Insecurity And Nutritional Status Among Women in Palm-Plantation Area of Kutai Kertanegara East Kalimantan (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Inability of individuals and household in providing adequate, nutritious and safe food will continue in conditions of food insecurity, which have an impact on malnutrition. Women play an important role in maintaining household food security while they are also vulnerable to food insecurity. This study aim to examine correlation between food insecurity and women nutritional status. This was a cross sectional study, with sample consist of 128 women in reproductive age who lived in palm plantation area in Kutai Kertanegara. The sampling technique was purposive. Food insecurity was assessed by the Radimer/ Cornell Hunger and Food Insecurity Instrument Questionnaire. The nutritional status of women measured by Body Mass Index and upper arm circumference. Bivariate Analysis was performed by Chi Square test. Household food insecurity was reported in 27.3% women, individual food insecurity was found in 29.7% women, and 8.6% child hunger. Bivariate analysis showed there is no significant correlation between food insecurity with nutritional status based on BMI or upper arm circumference. It should be made a comprehensive public health nutrition program to address food insecurity in remote area. Future studies would need more adequate study design and larger sample size to examine women nutritional status and food insecurity. Keywords : Food insecurity, nutritional status, palm-plantation